Evaluating the Relationship Between GPS Output and Planimetry System - Mohammad, A. R. A.; Hatim, A. J.; Sarsam, M.N.; Mohammed, K. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
. This       rtsearch      involveda     a  study  of     the     relationshipbetween GPS coordinates and  planimetry coordinates.     It         was found that  there is  a relation  between   GPS output coordinates andthe  coordinates of a distance point from the positi on of the GPS point. In order to pricist the direction of distance a reference point had beenused which is( Greenwich  Mean  observatory) GMO.The   angles   between   the  studying  points  and   Equator haveal so been calculated    Greenwich       line.     Also calculated the angle between every two regions have been calculated.